Identifikasi Koeksistensi Arsitektural pada Rumah Tradisional Walaka dan Bangunan DPRD di Kota Baubau (EMARA: Indonesian Journal of Architecture, 2018)
Coexistence in architecture was considered as the process of cooperation between two or more different architectural styles and synergized each others. The Old Buton society consists of Kaomu, Walaka, Maradika, and Batua. The social stratification system in Buton society was reflected in its dwelling. In the architectural context, various attempts to rediscover the identity in each of his work were very pronounced, with varying results. The study was aimed to identified coexistence between Walaka’s house and parliament building using a comparative causal approach. The results concluded that the coexistence between the Walaka’s houses and parliament building could be found in the form of philosophical, meanings, symbols, function on the modified floor plan, view, and sections.The coexistence between the house of Walaka’s with govermental position and parliament building could not be found between under the Walaka’s house and the parliament building foundation, tangkebala sasambiri and overstek console at parliament building and the Walaka’s box-shaped pabate and the overstek console from parliament building. The philosophical coexistence was also not founded between wide large and latticed windows at Walaka’s house with ones at parliament building, the Walaka’s bosu bosu and the overstek console without ornament at parliament building, as well as the Walaka’s double-decker roof and the parliament’s double-decker roof.